ANALISIS KAFALAH DAN QARDH DI INDONESIA - Asriadi, Ari; Asmuni, Asmuni; Anggraini, Tuti (JURNAL ILMIAH EDUNOMIKA, 2024)
An Islamic bank is a type of financial institution that operates by Islamic principles and rules and provides various banking services using different types of contracts or agreements that comply with Sharia law. These banks, in terms of Islamic banking, Qardh contracts are one of the most commonly used contracts. This study aims to engage the effect of the kafalah (guarantee or surety) component and the role of loan capital in implementing the qardh concept. Time series data obtained from the Financial Services Authority from 2018 to 2022 is used for this quantitative research. This study used multiple linear regression as the analysis to evaluate the effect. The results show that the Kafalah variable does not significantly impact the Qardh variable. Although the two types of contracts are most commonly used in Islamic banking practices, the main difference between them lies in the way they are implemented and applied. In Islamic bank guarantee products, the contract is known as kafalah. Qardh variables are affected by the loan capital. Qardh contracts do not impose any reward on the borrower of money or the recipient of assets. Due to its nature, the Qardh contract does not aim to generate financial profit; instead, it aims to help small businesses, social causes, and other organizations.